Crises at Work : Economy, Climate and Pandemic - Williams, Steve; Erickson, Mark (Understanding Work and Employment Relations, 2024)
It is impossible to view the news at present without hearing talk of crisis. This timely book looks at how three major crises - the economy, pandemic and climate - are related to the crisis of work, making it more precarious, intense and unequal. Providing an original and critical synthesis of recent trends in the field, expert scholars offer a programme for transcending the crisis of work. Offering a timely contribution to understanding the important issues facing the world, this book presents an important new way of thinking about work in contemporary societies.